Coexistence of pemphigus foliaceus and acquired hemophilia A: A case report. Issue 6 (9th April 2015) - Filipczak, Aleksandra; Michalska‐Jakubus, Małgorzata; Górska‐Kosicka, Magdalena; Woźniak, Katarzyna; Kowalewski, Cezary; Krupski, Witold; Pietrzak, Aldona; Wallner, Grzegorz; Mosiewicz, Jerzy; Lotti, Torello; Krasowska, Dorota
Abstract Pemphigus foliaceus (PF) is an autoimmune bullous dermatosis with anti‐desmoglein‐1 autoantibodies. Acquired hemophilia A (AHA) is a rare coagulation disorder with a high mortality rate, caused by anti‐factor VIII immunoglobulin G antibodies leading to spontaneous severe hemorrhages into skin, muscles or soft tissues. This coagulopathy may be associated with malignancies, drug reactions and autoimmune disorders including bullous dermatoses. Herein, we demonstrate a first report of AHA in the course of pemphigus foliaceus. A 55‐year‐old woman presenting with extensive, erosive, crusted, scaly skin lesions was diagnosed with PF based on histopathological and immunofluorescent examination, confirmed by the presence of anti‐desmoglein‐1 antibodies on enzyme‐linked immunoassay. She developed extensive internal hemorrhages and prolonged external bleeding after laparotomy. Based on coagulation tests, AHA was diagnosed. Simultaneous remission of pemphigus and coagulopathy occurred with immunosuppressants and recombinant activated factor VII.